(untitled) (Global Journal of Human-Social Science, 2020)
Introduction-Concerns about the possible effe cts of the mass media on individuals and cultures have been a preoccupation of academic research since World War 11. The Electronic colonialism Theory posits that mass media when exported carry with them broad range of values. These values are economic, social, cultural and sometimes political or religious in nature. Increasingly, they carry with them the English language in terms of music, movies, or the Internet. The World Systems theory elaborates and extends the Electronic Colonialism Theory (ECT) further by dividing the nations of the globe into three categories; it then expands on how the core category works to influence the two subordinate categories. However, within the Core nations, some are concerned about the impact and penetration of ECT as well, countries such as Canada, France, the U.K, Israel, New Zealand and Australia are prime Core nations that continually worry about the Americanization of their domestic cultural industries and consumer behavior (McPhail: 2010: 35).